Exploring perceptions of chronic neuropathic pain in spinal cord injured persons - Henwood, Penelope Kathleen (University of Ottawa (Canada), 2004)
The purpose of this thesis was to explore the effects of chronic neuropathic pain (CNP) and the process of acceptance of pain as it relates to adjustment to CNP in spinal cord injured (SCI) persons. The participants in two qualitative studies were community-living SCI persons who have CNP. They were currently or had previously received treatment at the out-patient clinic of a regional rehabilitation center. The first study involved a constant comparative analysis of narrative data obtained during three focus groups with 24 SCI persons. The second study involved a grounded theory approach to develop a conceptual framework that describes the process of 'acceptance' of CNP in SCI persons. The data was obtained during in-depth interviews with seven SCI persons with CNP. In Study 1, four interrelated themes emerged that illustrate the multidimensional impact of CNP in SCI. These themes include 'nature of pain', 'coping', 'medication failure', and 'pain impact'. In Study 2, the basic social process to describe acceptance of pain was 'moving forward with pain'. (Abstract shortened by UMI.)
Keywords: Health Sciences, Nursing.